2018
DOI: 10.1016/j.neuro.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential copper-induced death and regeneration of olfactory sensory neuron populations and neurobehavioral function in larval zebrafish

Abstract: Fish rely heavily on their sense of smell to maintain behaviors essential for survival, such as predator detection and avoidance, prey selection, social behavior, imprinting, and homing to natal streams and spawning sites. Due to its direct contact with the outside environment, the peripheral olfactory system of fish is particularly susceptible to dissolved contaminants. In particular, environmental exposures to copper (Cu) can cause a rapid loss of olfactory function. In this study, confocal imaging of double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…We next wanted to define the precise roles that the olfactory system and the lateral line each play in the generation of salt avoidance behaviors. To do this, we incubated larvae in various concentrations of copper sulfate, which kills cells in both the lateral line 27 and olfactory epithelia 28 . After treatment and recovery periods, we examined the larvae's behavioral responses to 50 mM NaCl pulses and found their reaction rate decreased with increasing copper concentration (4A).…”
Section: Olfactory Input Is Necessary To Drive Nacl Avoidance Behaviormentioning
confidence: 99%
“…We next wanted to define the precise roles that the olfactory system and the lateral line each play in the generation of salt avoidance behaviors. To do this, we incubated larvae in various concentrations of copper sulfate, which kills cells in both the lateral line 27 and olfactory epithelia 28 . After treatment and recovery periods, we examined the larvae's behavioral responses to 50 mM NaCl pulses and found their reaction rate decreased with increasing copper concentration (4A).…”
Section: Olfactory Input Is Necessary To Drive Nacl Avoidance Behaviormentioning
confidence: 99%
“…These olfactory alterations correlate with a long-term decrease in alarm and avoidance responses [88,114,115,116,117,118,119]. Exposure to Copper (Cu) causes marked OSN death, with a preferential loss of ciliated in comparison to microvillous OSNs; impairs the transcription of a wide variety of genes involved in olfactory processing, such as ORs and ionic channels; and reduces the recognition of bile salts while impairing odor-mediated alarm responses [120,121,122,123,124]. Cobalt (Co) is a naturally occurring and essential metal at low concentrations, but it is an environmental contaminant when found in high concentrations.…”
Section: The Olfactory System Of Zebrafish As a Model Of Neuroplasmentioning
confidence: 99%
“…It has been proposed that microvillous OSNs, which respond to amino acids, may present protective mechanisms that render them more resistant to damage, in order to preferentially preserve food sensing and feeding behaviors. It has also been suggested that these neurons may be replaced faster or in greater numbers and, therefore, their numbers do not plunge following olfactory epithelium damage [19,22,124].…”
Section: The Olfactory System Of Zebrafish As a Model Of Neuroplasmentioning
confidence: 99%
See 2 more Smart Citations